RELASI PEREMPUAN DAN LAKI-LAKI MENURUT LUCE IRIGARAY - Frederik Masri Gasa; Priskardus Hermanto Candra (Jurnal Harkat : Media Komunikasi Gender, 2020)
Abstract. In the culture of Manggarai-Flores the role of women is defined as ‘ata pe’ang (outsiders). This definition is followed by a series of obligations that must be imposed on women. In this pattern, the position of women in cultural practice is very weak and even women accept it as a matter of obedience to customs and culture. Through the lense of Luce Irigaray's sexual differences ethics, this paper intends to provide interruption to redefine the role and position of women who are culturally marginalized. Irigaray's idea became a means to map the differences between women and men. This difference is not a tool to compare the superiority of men over women but to make it a virtue inherent in both men and women. The appreciation of sexual differences is an entry point for dialogical relations between men and women. The ethical notion of Irigaray's sexual differences is truly relevant to the cultural context of Manggarai-Flores, especially in breaking the chain of and identifying violence against women, both visible and hidden (symbolic violence) as well as those originating from cultural determination. Abstrak. Dalam budaya Manggarai-Flores peran perempuan didefinisikan sebagai ‘ata pe’ang (pihak luar). Pendefinisian tersebut diikuti dengan serentetan kewajiban yang harus dibebankan kepada anak perempuan. Dalam pola seperti ini kedudukan perempuan dalam praksis budaya menjadi sangat lemah bahkan perempuan menerimanya dengan dalil ketaatan pada adat dan budaya. Melalui pisau bedah etika perbedaan seksual Luce Irigaray, tulisan ini bermaksud  memberikan interupsi untuk meredefinisi peran dan posisi perempuan yang termarginal karena budaya. Gagasan Irigaray menjadi alat untuk memetakan perbedaan antara perempuan dan laki-laki. Perbedaan tersebut bukan sebagai alat untuk membandingkan keunggulan laki-laki atas perempuan tetapi menjadikannya sebagai keutamaan yang melekat baik pada laki-laki maupun perempuan. Penghargaan terhadap perbedaan seksual  merupakan pintu masuk bagi relasi dialogis antara kaum laki-laki dan perempuan. Gagasan etika perbedaan seksual Irigaray ini sangat relevan untuk konteks budaya Manggarai-Flores khususnya dalam memutus mata rantai dan mengidentifikasi kekerasan terhadap perempuan baik yang kasat mata maupun yang tersembunyi (kekerasan simbolik) serta bersumber dari determinasi buday.